Taking initiative in market creation – a business ecosystem actor perspective. (1st January 2012) - Pellinen, Antti; Ritala, Paavo; Järvi, Kati; Sainio, Liisa-Maija
The purpose of this paper is to examine the role of taking initiative in developing next generation communication services. Focusing on different actors in our analysis, we adopt a business ecosystem perspective, where the role of network effects and interoperability are seen as prerequisites for market creation. In order to create new markets, however, certain actors need to take the initiative and subsequent risks. We provide an exploratory case study on IP multimedia subsystem (IMS) technology, which shows that taking initiative by different actors differ significantly in various phases of the development of new communication offerings. Thus, it is important to recognise that there is not only a need for a hub firm to lead the development as a whole, but more likely there is a need for several actors taking the initiative in the right time and at the right place.